Pengaruh Latihan Ayunan Tangan dengan Bantuan Pull Buoy terhadap Kecepatan Renang Gaya Bebas pada Anak Usia 7-9 Tahun di Swimming Performance Surabaya - Rosita, Claudia Rika; Sudijandoko, Andun (SPRINTER: Jurnal Ilmu Olahraga, 2025)
This study aims to determine whether arm swing training using a pull buoy affects the improvement of freestyle swimming speed in children aged 7–9 years at Swimming Performance Surabaya. This research employs a quantitative one-group pre-test-post-test design, involving a single experimental group (without a control group) that undergoes a pre-test, treatment, and post-test. The sampling technique used is purposive sampling, with 11 participants. Data analysis was conducted using the Shapiro-Wilk normality test and the Paired Sample T-Test hypothesis test through SPSS 25 software. The results indicate an increase in swimming speed for all participants in the post-test compared to the pre-test. The average pre-test speed was 45.37182, while the average post-test speed was 45.15455, with a difference of 0.217273. Therefore, it can be concluded that arm swing training using a pull buoy has an effect on freestyle swimming speed in children aged 7–9 years at Swimming Performance Surabaya. The change in average speed also suggests an improvement in the participants' performance.